Practice of applying visual advertising to Lithuanian contemporary art - Peseckienė, Dovilė (Vilnius University Open Series, 2019)
Visual advertising has become common part of our daily life in the past few decades. It is not only used  for commercial, political or social purposes, but also for the implementation of artistic strategies. Specific constructed artworks, exhibitions and art projects situated in a special/unconventional public spaces (context or semiosphere) are used as a tool to seek more spectators and spread different messages with critical, ironical, social connotations which leads to the deeper communication with spectators. They cannot avoid them because the messages interrupt their minds accidentally passing by the streets and so involve in the active interaction process. Art full of advertising strategies criticises the consumerist society created by advertising, and provokes the subject to take on an active position with respect to raised problems, i.e., it acts in the ideological field of contemporary/postmodern art.
Keywords: contemporary/postmodern art; visual advertising; visual communication; semiosphere; spectator